(untitled) (Kuala Lumpur, 1992)
This represents the largest single collection of blackwater species and new records. 101 species of fish were obtained, about 40% of the known fish fauna of Peninsular Malaysia,...
Keywords: Fishes,Aquatic animals,Wildlife conservation,Cá; Malaysia,North Selangor Peat Swamp Forest (Selangor),Malaysia,North Selangor Peat Swamp Forest (Selangor),Malaysia,North Selangor Peat Swamp Forest (Selangor),Malaysia